Behavior in organizations: an experimental approach - Lau, James B. (United States of America. McGraw-Hill Companies, Inc., 1996)
"The sixth edition of this book is the outcome of ongoing dialogues with colleagues, students, and managers, all of whom share the fascination with fostering adult learning and discovery. We wish to acknowledge the many scholars, managers, and researchers who contributed to the text. We are indebted to all those individuals who granted permission for the use of figures, tables, cases, simulations, and activities. The rich input from many of the adopters of the book on how to continuosly improve this product is appreciated. Their book was shaped significantly by three colleagues: David Peach, Michael Stebins, and Roger Conway at Calpoly State University. They have shared and put into practice a common belief that experiential learning is a synergistic and exhilarating way to each and learn about organizational behavior and management."
Includes bibliographical references.
English text.